2019
DOI: 10.3390/cells8040370
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway in Prostate Cancer

Abstract: Despite recent efforts, prostate cancer (PCa) remains one of the most common cancers in men. Currently, there is no effective treatment for castration-resistant prostate cancer (CRPC). There is, therefore, an urgent need to identify new therapeutic targets. The Hippo pathway and its downstream effectors—the transcriptional co-activators, Yes-associated protein (YAP) and its paralog, transcriptional co-activator with PDZ-binding motif (TAZ)—are foremost regulators of stem cells and cancer biology. Defective Hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 208 publications
(333 reference statements)
2
92
0
Order By: Relevance
“…Moreover, cellular stress signals, [32][33][34][35] as well as metabolism and nutrient signals, [36][37][38][39][40][41] also contribute to the regulation of the Hippo pathway. Disruption of the Hippo pathway causes tissue overgrowth and confers principal features of cancer, [42][43][44] including increased cell proliferation and survival, 45) abnormal cell division, 46,47) and enhanced cell migration. 48,49) In contrast, aberrant activation of the Hippo pathway impairs tissue development, stem cell maintenance, and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cellular stress signals, [32][33][34][35] as well as metabolism and nutrient signals, [36][37][38][39][40][41] also contribute to the regulation of the Hippo pathway. Disruption of the Hippo pathway causes tissue overgrowth and confers principal features of cancer, [42][43][44] including increased cell proliferation and survival, 45) abnormal cell division, 46,47) and enhanced cell migration. 48,49) In contrast, aberrant activation of the Hippo pathway impairs tissue development, stem cell maintenance, and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent findings demonstrated that YAP/TAZ and AR signaling serve as the central regulatory mechanisms for prostate tumorigenesis and several cancer-associated pathways can promote YAP/TAZ signaling (14,42). However, the complete mechanism by which YAP/TAZ signaling becomes hyperactivated and interacts with the stroma, as well as their precise role in PCa development, has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of YAP or TAZ or their nuclear localization is observed significantly more frequently in mCRPC than in primary PCa, and disruption of YAP/TAZ or AR signaling suppresses the castration-resistant growth, motility, and invasion of PCa cells (12)(13)(14)(15). Elevated YAP/TAZ signaling is also a positive regulator of AR signaling, and it responsible for CR and metastasis, indicating the significance of YAP/TAZ signaling in PCa progression (12,15).…”
Section: Introductionmentioning
confidence: 99%
“…The FA metabolism related pathways, PPAR signaling pathway, and cell adhesion-related hub genes and pathways were already discussed above. It was demonstrated that he activation of Hippo signaling pathway regulates cell growth and proliferation by inhibiting YAP and TAZ transcription co-activators, and its dysregulation impacts significantly on development of cancers including colon, liver, breast, lung, ovary, and prostate (Salem & Hansen 2019;Yu et al 2015).…”
Section: Discussionmentioning
confidence: 99%